Polysaccharides from natural resources exhibit great potential in the treatment of ulcerative colitis: A review. (15th February 2021) - Niu, Wei; Chen, Xiaoqing; Xu, Ruling; Dong, Huimin; Yang, Fuyan; Wang, Yun; Zhang, Zhenhai; Ju, Jianming
Highlights: Ulcerative colitis (UC) is a debilitating disease with a high incidence. New drug with better efficacy and safety profile than existing therapies is needed. Polysaccharides have been shown to exert a positive therapeutic effect on UC. The current knowledge and future potential of polysaccharides in UC were analyzed. Abstract: The incidence of ulcerative colitis (UC) is high. Despite the availability of various therapeutic agents for the treatment of UC, the routine treatment has limitations and serious side effects. Therefore, a new drug that safely and effectively treats UC is urgently needed. Polysaccharides from natural resources have recently become a hot topic of study for their therapeutic effects on UC. These effects are associated with the regulation of inflammatory cytokines, intestinal flora, and immune system and protection of the intestinal mucosa. This review focuses on the recent advances of polysaccharides from natural resources in the treatment of UC. The mechanisms and practicability of polysaccharides, including pectin, guar gum, rhamnogalacturonan, chitosan, fructan, psyllium, glycosaminoglycan, algal polysaccharides, polysaccharides from fungi and traditional Chinese medicine, and polysaccharide derivatives, are discussed in detail. The good efficacy and safety of polysaccharides make them promising drugs for treating UC.